2010
DOI: 10.1007/s10719-010-9297-y
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic globotriaosylceramide analogue inhibits HIV-1 infection in vitro by two mechanisms

Abstract: Previously, it was shown that the cell-membrane-expressed glycosphingolipid, globotriaosylceramide (Gb(3)/P(k)/CD77), protects against HIV-1 infection and may be a newly described natural resistance factor against HIV infection. We have now investigated the potential of a novel, water soluble, non-toxic and completely synthetic analogue of Gb(3)/P(k) (FSL-Gb(3)) to inhibit HIV-1 infection in vitro. A uniquely designed analogue, FSL-Gb(3), of the natural Gb(3)/P(k) molecule was synthesized. HIV-1(IIIB) (X4 viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
4
28
1
Order By: Relevance
“…In addition to the modification of cell and virion surfaces FSL constructs can also be infused directly into the circulation of laboratory animals causing in vivo modification of circulating cells 7 and to inhibit viruses 12 , toxins, 12 and antibodies 7 . FLS constructs have also been used to decorate liposomes and can be printed onto paper surfaces 13 , where they immobilize, and can then be used in diagnostic assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the modification of cell and virion surfaces FSL constructs can also be infused directly into the circulation of laboratory animals causing in vivo modification of circulating cells 7 and to inhibit viruses 12 , toxins, 12 and antibodies 7 . FLS constructs have also been used to decorate liposomes and can be printed onto paper surfaces 13 , where they immobilize, and can then be used in diagnostic assays.…”
Section: Discussionmentioning
confidence: 99%
“…FSL construct functional moieties (F) so far include a range of saccharides including blood group-related determinants, sialic acids, hyaluronan polysaccharides, fluorophores, biotin, radiolabels, and a range of peptides [3][4][5][6][7][8][9][10][11][12] . FSL constructs have been used in modifying embryos, spermatozoa, zebrafish, epithelial/endometrial cells, red blood cells, and virions to create quality controls systems and diagnostic panels, to modify cell adhesion/ interaction/ separation/ immobilization, and for in vitro and in vivo imaging of cells/virions [3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…animal studies have shown no toxicity at millimolar quantities systemically. The unusual tail also allows for this analogue to insert itself into cell membranes and convert an HIV-permissive Gb 3 -negative T-cell into a Gb 3 -positive T-cell that resists HIV infection (Harrison et al, 2010 (Harrison et al, 2010). This was shown both for laboratory strains of HIV-1 as well as for clinical isolates of R5 HIV-1 viruses.…”
Section: Fsl-gbmentioning
confidence: 99%
“…A completely synthetic water soluble analogue of Gb 3 termed Functional head Spacer Lipid tail-Gb 3 (FSL-Gb 3 ) was shown to inhibit X4 and R5 HIV-1 infection with a similar 50% inhibitory activity (IC 50 ) as adaGb 3 (Harrison et al, 2010). This Gb 3 analogue was unique in that the lipid tails were replaced with phosphatidylethanolamine and a spacer region containing multiple ionic residues allowed for complete solubility in aqueous media.…”
Section: Fsl-gbmentioning
confidence: 99%